Changes of biochemical factors and the effect on recurrence of medullary thyroid carcinoma after surgery - Fengli Guo; Lijuan Li; Pengfei Gu; Guoqiang Zhang; Xianhui Ruan; Jingzhu Zhao; Xiangqian Zheng; Songfeng Wei; Ming Gao (Heliyon, 2024)
Objective: Medullary thyroid carcinoma (MTC) is a rare malignancy secreting calcitonin (Ctn). We aimed to analyze the relationship between Ctn levels at different time points in patients with MTC, and evaluate its predictive effect on recurrence. Methods: A retrospective study of patients diagnosed with MTC in a large medical center were conducted in northern China. The interrelationships between preoperative Ctn, normalization of postoperative serum Ctn at the first month (NPS), and long-term biochemical cure as well as their predicting roles on structural recurrence were assessed. Results: A total of 212 patients were included in this study. The median follow-up time was 59.5 months. The 5- and 10-year cumulative disease-free survival rates were 81.5 % and 66.8 %, respectively. NPS (OR: 216.33, 95 % CI: 28.69–1631.09, P < 0.001) and absence of structural recurrence (OR: 61.71, 95 % CI: 3.90–975.31; P = 0.003) were associated with biochemical cure. Non-biochemical cure (OR: 28.76; 95 % CI: 2.84–290.86; P = 0.004, HR: 14.63, 95 % CI: 2.27–94.07, P = 0.005), larger tumor size (OR: 8.79, 95 % CI: 2.12–36.40, P = 0.003, HR: 5.41, 95 % CI: 2.04–14.37, P = 0.001), and multifocality (OR: 4.02, 95 % CI: 1.06–15.17, P = 0.040, HR: 3.00, 95 % CI: 1.18–7.60, P = 0.021) were unfavorable independent predictors of structural recurrence and disease-free survival. For sporadic MTC confined to the thyroid lobe, there was no difference in biochemical or structural prognosis between the different surgeries in the subgroup analysis. Conclusions: NPS, rather than preoperative Ctn, predicted long-term biochemical cure for MTC. Non-biochemical cure, larger tumor burden including larger tumor size and multifocality at initial surgery, served as worse prognostic predictors.